Pengaruh waktu penggantian ransum BR 1 dengan BR 2 terhadap bobot potong, bobot karkas, dan lemak abdominal broiler - Pandu Purnama; Syifa Nurjannah; Nilawati Widjaya; Tedi Akhdiat; Hilman Permana (Fakultas Pertanian Universitas Majalengka, 2023)
This research aimed to see how the impact of time to replace BR 1 with BR 2 ration to slaughtering weight, carcass weight, and abdominal fats of broiler. This research was an experimental method using Complete Randomized Design (CRD) with five treatments and five replication. These treatment consisted of P1: giving BR 1 (1 to 42 days old), P2: giving BR 2 (1 to 42 days old), P3: giving BR 1 (1 to 7 days old), and giving BR 2 (8 to 42 days-old), P4: giving BR 1 (1 to 14 days-old) and giving BR 2 (15 to 42 days-old), P5: giving BR 1 (1 to 21 days-old) and giving BR 2 (22 to 42 days-old). The observed variables were slaughtering weight, carcass weight, and abdominal fats of the broiler. The collected data were analyzed by ANOVA and Duncan's test. The results showed that various feeding timing techniques from starter feed (BR1) to grower feed (BR2) did not make a significant difference (p>0.05) in broiler slaughter weight, carcass weight, and abdominal fat. Each of these weights is in the range of 2617.86 – 2754.24 g/head; 2010.51 – 2076.69 g/head or 75.00 – 76.80%; and 41.70 – 44.40 g/head. It can be concluded that all techniques when changing feed types from BR1 to BR2 can be carried out by breeders, however, the economic value of these techniques must be considered because the two types of feed have different prices.